If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(7xy + -11) + 4(5xy + 6) = 0 Reorder the terms: -1(-11 + 7xy) + 4(5xy + 6) = 0 (-11 * -1 + 7xy * -1) + 4(5xy + 6) = 0 (11 + -7xy) + 4(5xy + 6) = 0 Reorder the terms: 11 + -7xy + 4(6 + 5xy) = 0 11 + -7xy + (6 * 4 + 5xy * 4) = 0 11 + -7xy + (24 + 20xy) = 0 Reorder the terms: 11 + 24 + -7xy + 20xy = 0 Combine like terms: 11 + 24 = 35 35 + -7xy + 20xy = 0 Combine like terms: -7xy + 20xy = 13xy 35 + 13xy = 0 Solving 35 + 13xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 13xy = 0 + -35 Combine like terms: 35 + -35 = 0 0 + 13xy = 0 + -35 13xy = 0 + -35 Combine like terms: 0 + -35 = -35 13xy = -35 Divide each side by '13y'. x = -2.692307692y-1 Simplifying x = -2.692307692y-1
| 6*(x-10)+3*(2x-7)=45 | | 3x=7-9 | | 6-6x=9-7x | | 18p+21q+9= | | 6x^2-8x=l | | 2(2x-1)=4 | | 8m-20=-9m+30 | | 4m^2-3m+19=12 | | 3x^2+7x+1=12 | | 6-5x=4-3x | | 5t-10=2t-1 | | 8(2c-5)= | | B^2+12b+36=0 | | 3x+35=10x-35 | | 8x+3-8x=5x+2 | | 96-3x=10x-18 | | 9-9x=31-16x | | 8-(5x+8)=7+2x | | k^2+1=12 | | 6x+33=13-37 | | 4n^2+6=8n | | 8a-wd=-3 | | .42x+6=3x | | (4)(-3)= | | 18x-3=7x+2 | | 75.34+b+41.1=28.946 | | 7n^2+3n=11 | | 6x+33=3x-37 | | 2x+17-x=8+5x-7 | | (3n+10)=5n-10+6n | | 19x-3=8x+30 | | 94-2x=25x+22 |